Examining the Authority Relationship Between the Center and Regions in Determining Policy Authority and Regional Interests - Ahmad Rusly Purba (Faculty of Law, Universitas Pekalongan, 2023)
The relationship between the central and regional governments always has an integrated hierarchical connection. This relationship is linked in the documents of the National Medium-Term Development Plan (RPJMN) and the Regional Medium-Term Development Plan (RPJM Daerah). The integration of regional authority is an extension of central authority, encompassing the management and formulation of policies, financial management, as well as the management of natural resources owned by the region. All these authorities share the common goal of enhancing the region's capability to realize progress and self-reliance. Governance is related to functions such as leading, guiding, commanding, mobilizing, coordinating, supervising, and motivating in governance relationships. In modern governance, some experts categorize government functions into four parts: services (public service), development, empowerment, and regulation. If the government can effectively carry out its functions, it is assumed that services will lead to justice, empowerment will result in self-reliance, and development will create prosperity. Ultimately, in its implementation, regional autonomy is a partial decentralization of authority from the central government to the regional government to be independently managed as their domestic affairs. Granting autonomy to regions must be based on factors that ensure the concerned region is capable of managing its own household.